Peranan Sekretaris Desa dalam Menunjang Kinerja Kepala Desa di Desa Sembahe Baru Kecamatan Pancur Batu Kabupaten Deli Serdang - Elvida Br Tarigan; Muhammad Husni Thamrin Nasution; Rosmala Dewi (Universitas Medan Area, 2017)
Village Secretary beam is a device that helps the Village Head of Government in the field of orderly administration and development as well as service and community empowerment. As Village Secretary, whose main task is to regulate and manage the financial administration and secretarial affairs inside the container structure of village government organizations, as well as helping the task of village head in governance, social services and rural development. The purpose of this study was to determine the role of Village Secretary Assisting the Head of the Village as well as the constraints. This study leads to the village secretary function to assist the village chief in village governance.this study is a descriptive study with a qualitative approach that describes the phenomenon of the field an then analyzing the facts. The data used is more dominant secondary data fitted with interviews and observations and research was conducted in the village and the Sembahe Baru village office. Based on the analysis of all sources of Informants collected in accordance with the needs of research, the role of the secretary of the village in the village head here helps researchers can conclude from the research that has been good enough role in helping chief Secretary Rural village in Sembahe Baru village.